2009
DOI: 10.1016/j.jmb.2009.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Domains Control the Active-State Stoichiometry of Aquifex aeolicus σ54 Activator NtrC4, as Revealed by Electrospray Ionization Mass Spectrometry

Abstract: A common challenge with studies of proteins in vitro is determining which constructs and conditions are most physiologically relevant. σ 54 activators are proteins that undergo regulated assembly to form an active ATPase ring that enables transcription by σ 54 -polymerase. Previous studies of the AAA+ ATPase domains from σ 54 activators have shown that some are heptamers, while others are hexamers. Because the active oligomers assemble from off-state dimers, it was thought that even-numbered oligomers should d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 75 publications
1
43
0
1
Order By: Relevance
“…Upon phosphorylation/activation they form higher-order oligomeric states (hexamer or heptamer) triggered by oligomerization of a central σ54 binding ATPase domain. These ring-like structures induce open complex formation of RNA polymerase [166]. …”
Section: Response Generationmentioning
confidence: 99%
“…Upon phosphorylation/activation they form higher-order oligomeric states (hexamer or heptamer) triggered by oligomerization of a central σ54 binding ATPase domain. These ring-like structures induce open complex formation of RNA polymerase [166]. …”
Section: Response Generationmentioning
confidence: 99%
“…In full-length NtrC1, the equilibrium between heptamer and hexamer rings may be influenced by the presence of the N-terminal two-component receiver and C-terminal domains. Mass spectroscopy data showed that hexamer is favored over heptamer in fulllength constructs of NtrC4, an EBP related to NtrC1 (Batchelor et al 2009). The receiver domain forms stable homodimers, and the C-terminal DNA-binding domain directs assembly of four protomers in a tandem array on ''enhancers'' (Doucleff et al 2005;Vidangos et al 2013).…”
Section: Crucial Asymmetry In Bebp Atpase Ring Genes and Development 2505mentioning
confidence: 99%
“…For example, NtrC4 (a σ activator protein from Aquifex aeolicus ) requires millimolar concentrations of certain salts, e.g., Mg 2+ , BeF 3 − , and ADP, in order to assemble into an active hexamer. 35, 36 Several techniques for reducing sodium ion adduction to proteins in ESI have been developed that do not require removal of the salts from solution prior to ion formation. Buffer loading, 21, 22 in which high concentrations of a volatile buffer, typically ammonium acetate, is added to solution, reduces sodium ion adduction to proteins and reduces the number of salt ion clusters formed.…”
Section: Introductionmentioning
confidence: 99%